Q-switched Tm³⁺-doped multi-ring fibre laser operating at 1.96 μm - Sójka, Łukasz; Pajewski, Łukasz; Sujecki, Sławomir; Lamrini , Samir; Prorok, Mateusz; Miluski, Piotr; Kochanowicz, Marcin; Łodziński , Marek; Pisarski, Wojciech A.; Dorosz, Dominik (Opto-Electronics Review, 2025)
A realisation of a Q-switched Tm3+-doped fibre laser operating at 1.96 μm wavelength is reported. The Tm3+-doped fibre was fabricated using a novel multi-ring modified chemical vapour deposition-chelate doping technique (MCVD-CDT) technology. The developed laser emits pulses at a repetition rate of 3 kHz with an energy of 84 μJ and a duration of 272 ns, which corresponds to a peak power of 304 W. The experimental results confirm that the fabricated Tm3+-doped multi-ring, large mode area fibre is a promising candidate for developing high-energy Q-switched lasers operating near 2 µm wavelength.